+0  
 
0
125
1
avatar

Simplify $(1-2i)(1-i)(1+i)(1+2i)$.

Guest Feb 2, 2018
 #1
avatar
+1

Simplify the following:

(-2 i + 1) (-i + 1) (i + 1) (2 i + 1)

 

(1 - 2 i) (1 - i) = 1×1 + 1 (-i) + -2 i×1 + -2 i (-i) = 1 - i - 2 i - 2 = -1 - 3 i:

-3 i - 1 (1 + i) (2 i + 1)

 

Factor -1 from -3 i - 1:

-(3 i + 1) (1 + i) (2 i + 1)

 

(1 + 3 i) (1 + i) = 1×1 + 1 i + 3 i×1 + 3 i×i = 1 + i + 3 i - 3 = -2 + 4 i:

-4 i - 2 (2 i + 1)

 

Factor 2 out of 4 i - 2 giving 2 (2 i - 1):

-2 (2 i - 1) (2 i + 1)

 

(-1 + 2 i) (1 + 2 i) = -1 - 2 i + 2 i×1 + 2 i×2 i = -1 - 2 i + 2 i - 4 = -5:

-2×-5

 

-2 (-5) = 10

Guest Feb 2, 2018

29 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.